1995
DOI: 10.1007/bf01254572
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m-tetrofosmin uptake in malignant lung tumours

Abstract: Technetium-99m-tetrofosmin is a new myocardial imaging agent which has yielded promising results compared to thallium-201. The tumour-seeking properties of the routinely used cardiac radiopharmaceuticals 201TI and 99mTc-methoxyisobutylisonitrile are well known. Here we report the results of a pilot study demonstrating 99mTc-tetrofosmin uptake in malignant lung tumours. Five patients with bronchial carcinoma, each in different stages of chemo- or radiotherapy, were imaged. Dynamic and static acquisitions were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…The precise mechanisms of uptake of 99mTc-tetrofosmin by tumor tissue has not been sufficiently elucidated, but its tumor localization may be explained on the basis of such factors as regional blood flow and mitochondrial content. 1,21 In addition, it was also reported that accumulation of this tracer in breast tumor cells in vitro is related to the P-glycoprotein similar to MIBI. 22 99m Tc-MDP scintigraphy is an excellent method for delineating tumor-bearing lesions in the whole body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanisms of uptake of 99mTc-tetrofosmin by tumor tissue has not been sufficiently elucidated, but its tumor localization may be explained on the basis of such factors as regional blood flow and mitochondrial content. 1,21 In addition, it was also reported that accumulation of this tracer in breast tumor cells in vitro is related to the P-glycoprotein similar to MIBI. 22 99m Tc-MDP scintigraphy is an excellent method for delineating tumor-bearing lesions in the whole body.…”
Section: Discussionmentioning
confidence: 99%
“…MANY AUTHORS have reported that 99mTc-tetrofosmin is useful as tumor-seeking agent for lung, 1-6 breast,7-t 0 thyroid' [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and other malignant tumors. [15][16][17][18][19][20] In some cases, not only the primary lesion but also its lymph node metastases were delineated in patients with lung cancer, thyroid cancer and breast cancer, but there is no report on the visualization of bone metastases from breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, Basoglu and coworkers reported a pilot study of five patients with bronchial carcinoma, in different phases of treatment, four of which showed a localized tumor uptake of 99m TC-tetrofosmin. 60 In their mature analysis, 39 a clear accumulation of the radiotracer was visibly present in 26 of 34 malignant tumors, but also in 3 of the 11 benign lesions. Of the 26 patients with malignant tumors accumulating 99m TC-tetrofosmin, 9 had repeated imaging 6 -8 weeks after radiochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Rambaldi et al [2] described the incidental detection of abnormal uptake in a patient with breast cancer undergoing myocardial scintigraphy with TF. Besides breast cancer, TF has been considered a radiopharmaceutical with a great deal of promise in the imaging of different cancers [3,4]. Blood flow, metabolic status of cells and tissue viability are important factors in cellular uptake of TF.…”
Section: Introductionmentioning
confidence: 99%